Estimation of (n, p) and (n, α) Cross Section of Radionuclide 60Co for Fusion Technology Applications. (19th May 2018) - Pandey, Jyoti; Pandey, Bhawna; Agrawal, H. M.; Subhash, P. V.; Vala, S.; Aiyyala, Akhil Sai; Makwana, Rajnikant; Suryanarayana, S. V.
Abstract: For fusion application, there is a high demand for nuclear data for long-lived radionuclides produced in a neutron environment. Cobolt-60 (t1/2 = 5.3 years) is one of the radionuclides produced in a large amount inside the fusion reactor via different pathways. In this context, the excitation function of 60 Co(n, p) and 60 Co(n, α ) reaction from threshold to 20 MeV has been calculated using TALYS-1.6 in the framework of the Hauser Feshbach statistical model along with preequilibrium effects. Outgoing (proton and alpha) particle energy spectra (d σ /dEp, d σ /dE α ) and double-differential cross section (d 2 σ /dE d Ω ) has also been estimated at 14 MeV incident neutron energy. Optimized input parameters used during the model calculation were determined by fitting the (n, p) and (n, α ) cross sections to the experimental data for the adjacent stable nuclide 59 Co. The activation analysis has also been carried out for 1 kg of stainless steel (SS316) using FISPACT-2007.